The History of English. - Bergs, Alexander; Brinton, Laurel (Mouton Reader, 2017)
This volume provides an in-depth account of Old English, organized by linguistic level. Individual chapters, written by recognized experts in the field, review the state of the art in phonological, morphological, syntactic, and semantic studies of Old English. Key areas of debate, including dialectology, language contact, standardization, and literary language, are also explored. The volume sets the scene with a chapter on pre-Old English and ends with a chapter discussing textual resources available for the study of earlier English.